ضوابط التسويق في الاقتصاد الإسلامي - سالمي, هنيه (University of eloued جامعة الوادي, 2015)
الحمد لله رب العالمين والصلاة والسلام على المبعوث رحمة للعالمين، وعلى آله وصحبه التابعين و بعد: هدفت هذه الدراسة إلى التعرف على ضوابط التسويق التي تحكم السوق في الإسلام، وإلى معرفة تحليل أجزاء النظام الاقتصادي الإسلامي العملي، وذلك بالكشف عن الحقائق الكامنة الموجودة فيه . وقد تضمن البحث مقدمة في البداية، وثلاثة فصول، وأشرنا من خلالها إلى ممهدات الموضوع، حيث تناولنا في الفصل الأول أساسيات حول الاقتصاد الإسلامي، واشتمل الفصل الثاني على مفاهيم أساسية للتسويق، أما الفصل الثالث المعنون بضوابط التسويق في الاقتصاد الإسلامي ويندرج تحته ثلاثة مباحث، المبحث الأول يتم فيه التعرف على الضوابط الفقهية، والمبحث الثاني نتناول فيه أهم الضوابط العقدية للتسويق، أما المبحث الأخير أي الثالث تطرقنا فيه إلى الضوابط الأخلاقية للتسويق. ومن أبرز النتائج التي توصلت لها هي: إن تطبيق مبادئ الاقتصاد الإسلامي في مجال التسويق يكون مسبوق بتطبيق  مفاهيم هذا النظام على مختلف المجالات الأخرى. وأن النشاط التسويقي يعد جزء من الاقتصاد الإسلامي، وبالتالي لا يمكن الفصل بين التسويق في الإسلام. الاقتصاد الإسلامي جزء من صيغة عامة للحياة فلا يجوز أن ندرس الاقتصاد  منفصلا عن سائر كيانات المذاهب الاجتماعية و السياسية، وعن طبيعة العلاقات القائمة بين تلك الكيانات، فإن النظر إلى شيء يجب أن يكون ضمن صيغة عامة. إن الاعتماد على تطبيق النظام الاقتصادي الإسلامي يحمي من الوقوع و  التعرض للأزمات المالية، والهزات الاقتصادية وذلك بانتهاج المنهج الإسلامي بالتزام الأخلاق في المعاملات المالية المشروعة. الملخص Praise be to Allah, prayer and peace envoy to the mercy to the worlds, and his family and companions and followers after: This study aimed to identify the marketing controls that control the market in Islam, and to analyze the practical knowledge of Islamic economic system parts, and that disclosure of the underlying facts in it. The research included the introduction at the beginning, and three chapters, and we pointed out from which to graders subject, where we dealt with in the first quarter basics about Islamic economics, and included the second chapter on the basic concepts of marketing, The third chapter, entitled controls marketing in Islamic economics and falls below three sections, The first section is the identification of doctrinal controls, and the second topic we address the most important Streptococcus marketing controls, and the last section of any third touched the controls to ethical marketing. Among the most prominent findings of her are: * The application of the principles of Islamic economics in the field of marketing is unprecedented application of the concepts of this system at various other areas. And that marketing activity is part of the Islamic economy, and therefore can not be separated from marketing in Islam. * Islamic economics is part of a general formula of life is not permissible to study separate from the other entities of the doctrines of social and political economy, and the nature of the relationships between those entities, the consideration to something must be within the general formula. * The dependence on the Islamic economic system protects the application from falling and exposure to financial crises, economic shocks and should be fostered by the commitment of the Islamic approach ethics in illegal financial transactions.
مذكرة ماستر معاملات مالية
Keywords: التسويق/الاقتصاد الإسلامي/; Marketing/Islamic Economy/